2018
DOI: 10.1128/aac.00649-18
|View full text |Cite
|
Sign up to set email alerts
|

Coidentification of mcr-4.3 and bla NDM-1 in a Clinical Enterobacter cloacae Isolate from China

Abstract: We describe the first report of a clinical colistin-resistant ST84 isolate coharboring (previously named ) and from a patient in China. The -harboring IncX3 plasmid and the novel-harboring ColE plasmid were completely sequenced. Although this isolate showed a high level of resistance to colistin, plasmid transformation, gene subcloning, susceptibility testing, and lipid A matrix-assisted laser desorption ionization mass spectrometry analysis indicated that itself does not confer resistance to colistin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
4
42
0
Order By: Relevance
“…CP000447), and mcr-4.3 showed 100% nucleotide identity to the sequence in the genome. These data supported the conclusion that mcr-4 and its alleles originated from Shewanella frigidimarina (6), while the identification of mcr-4.3 in A. baumannii resonated with the indication of horizontal gene transfer of mcr-4.3, according to the other two reports (14,15).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…CP000447), and mcr-4.3 showed 100% nucleotide identity to the sequence in the genome. These data supported the conclusion that mcr-4 and its alleles originated from Shewanella frigidimarina (6), while the identification of mcr-4.3 in A. baumannii resonated with the indication of horizontal gene transfer of mcr-4.3, according to the other two reports (14,15).…”
Section: Resultssupporting
confidence: 81%
“…We could not determine whether transfer of pAB18PR065 could confer resistance to colistin. According to the other two studies, mcr-4.3 alone did not confer phenotypic resistance to colistin (14) and showed a lack of lipid A modification function (15). Recently, a study on the action and mechanism of MCR-4 showed that revertants of mcr-4.3 (either V179G or V236F) led to its expression and conferred colistin resistance of 8 g/ml, together with the acquired function of lipid A modification (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For livestock and poultry, antibiotics usage may also varied with breeding scales and farms. In addition to mcr-1 and bla NDM−1 gene, other genotype combination were also reported from China (Kong et al, 2017;Liu et al, 2017b;Chavda et al, 2018;Wang R. et al, 2018). The mcr and bla NDM genes co-harbored isolates from China are often E.…”
Section: Discussionmentioning
confidence: 91%
“…As well, Enterobacter spp. are increasingly being isolated in many clinical infections in which they are found to as a major host of mcr colistin resistance genes and other clinically important MDR determinants 34,[37][38][39] (Tables S1-S3), which can be transferred to other intestinal pathogens 16,17,30 . Notably, the E. coli isolates also exhibited high resistance rates against important clinical antibiotics (Tables S1-S3).…”
Section: Discussionmentioning
confidence: 99%